Perbandingan Hasil Belajar Siswa Sd Di Perkotaan Dan Di Pedesaan Melalui Media Pembelajaran Berbasis Multimedia Flash Flip Book Pendidikan Kewarnegaraan - Meilia Nur Indah Susanti; Yessy Asri (KILAT, 2017)
Understanding of the nation's character and national insight is one of the absolute musts of Indonesian society to create unity and unity of the nation. However, after the New Order era when entering the beginning of the reform era, there began to degradation of community understanding related to national character and national insight. Although Indonesia in the era of reform has become the third largest democracy in the world, but without understanding the character and national identity and national insight is not enough to be a strong country. The era of globalization as one thing that is absolute and inevitable is one of the challenges for the life of nation and state in almost all countries, including Indonesia. So many emerging threats that are no longer in the form of conventional wars, but other threats that attack the concepts of thought and lifestyle of the community so that the love of the homeland faded. The young generation of this nation which is the root of a nation must know and respect the historical values ​​that have been laid down the founders of the nation. History continues to be written, in all civilizations and at all times, History in writing or documentation is an important tool in studying the progress and decline of a nation contained in events in the past. The purpose of this study is to determine the comparison of learning outcomes of elementary school students in urban as well as in rural areas through multimedia-based learning method flash flip book education civic education with quasi experimental studies pretest posttest design in improving character education nation and nationality insight amid ethnic, religious, and culture. SD Bani Saleh 5 Bekasi is an Islamic elementary school located in the center of Bekasi City which has facilities and infrastructure that support the learning process. SDN SetiaDarma Bekasi is SD Negri located in Bekasi Regency that is Tambun Selatan Bekasi whose learning activity is not supported by supporting facilities and infrastructures in learning process.